Ionic conduction of blend poly (vinylidene fluoride-hexafluoro propylene) and poly (methyl methacrylate)-grafted natural rubber based solid polymer electrolyte - Ataollahi N.; Ahmad A.; Hamzah H.; Rahman M.Y.A.; Mohamed N.S. (2023)
The complex of Poly (vinylidene fluoride-hexafluoro propylene) (PVDF-HFP), Poly (methyl methacrylate)-grafted natural rubber (MG49) (70/30) with lithium trifluoromethane sulfonate (LiCF3SO3) based solid polymer electrolyte has been prepared using solution casting technique. The electrochemical impedance spectroscopy (EIS) has been used to measure the ionic conductivity. This work has demonstrated that the addition of an optimum content of LiCF3SO3 enhance the ionic conductivity of polymer electrolyte films and conductivity values were found to depend upon the concentration of LiCF3SO3. The highest ionic conductivity achieved at 1.9710-4 S cm-1for 25 wt. % of LiCF3SO3 at room temperature. By applying the temperature range from 303 K to 373 K the conductivity rise and the maximum conductivity obtained at 5.6510-3 S cm-1 at 373 K. The interaction between Li ion and F atom in the structure of PVDF-HFP and O atom in MG49 resulting the formation of complex proved by the study of fourier transform infrared spectroscopy (FTIR). The amorphicity and crystallinity of electrolyte films have been characterized by x-ray diffraction (XRD) which indicates decrease in the degree of crystallinity by increasing of salt concentration. Scanning electron microscopy (SEM) appeals that there is no phase separation in the blend. Furthermore the nature of lithium salt has been found to influence the morphology of the polymer-blended electrolytes by improvement of surface morphology from rough to smooth with increasing salt content. 2013 by ESG.